Stakeholder engagement and the sustainable environmental management of oil-contaminated sites in Nigeria - Prpich, George; Sam, Kabari; Coulon, Frederic (Palgrave Macmillan, 2018)
African nations are experiencing rapid economic growth and development, particularly within the energy sector; however, this growth has come at a cost to the environment and society. Nowhere have these impacts been felt more precisely than in the oil and gas producing regions of Nigeria where years of neglect and mismanagement have resulted in vast areas of hydrocarbon contaminated lands. In this chapter, we present a case study of the Niger Delta. We show how constructive stakeholder engagement can be used to integrate the values and perspectives of affected communities and how this information can be used to inform environmental regulation and sustainable development. Lessons learned are relevant to other countries seeking to develop their energy resources in a sustainable manner.
Energy in Africa: Policy, Management and Sustainability
Keywords: stakeholder engagement; Niger Delta; Nigeria; oil pollution; policy transfer; contaminated land; environmental policy